Let's simplify step-by-step.
3x^2+x+5+2x^2+x−2
=3x^2+x+5+2x^2+x+−2
Combine Like Terms:
=3x^2+x+5+2x^2+x+−2
=(3x^2+2x^2)+(x+x)+(5+−2)
=5x^2+2x+3
Answer:=5x^2+2x+3
OR
3x*2+x+5+2x*2+x-2
Group like terms
2*3x+x+2*2x+x-2+5
Add similar elements: x+x=2x
2*3x+2x+2*2x-2+5
Refine
6x+2x+4x-2+5
Add similar elements: 6x+2x+4x=12x
12x-2+5
Add/Subtract the numbers: -2+5=3
=12x+3
Sorry, but I'm not 100% sure what you meant by 3x2 and 2x2. It could've made two different problems so that's what I did.
I hope this helps you and have a great day!! :)